2018
DOI: 10.7554/elife.39633
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pre-initiation complex in Mediator recruitment and dynamics

Abstract: The Mediator complex stimulates the cooperative assembly of a pre-initiation complex (PIC) and recruitment of RNA Polymerase II (Pol II) for gene activation. The core Mediator complex is organized into head, middle, and tail modules, and in budding yeast (Saccharomyces cerevisiae), Mediator recruitment has generally been ascribed to sequence-specific activators engaging the tail module triad of Med2-Med3-Med15 at upstream activating sequences (UASs). We show that yeast lacking Med2-Med3-Med15 are viable and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
77
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(94 citation statements)
references
References 84 publications
15
77
2
Order By: Relevance
“…We found that Taf1 occupancy was essentially unchanged upon simultaneous depletion of Kin28 and TBP (Fig. 4A); marked effects on Mediator and Pol II association provide evidence for efficient depletion of both Kin28 and TBP [21], as does the loss of the artifactual, transcription-dependent signal at the 3' ends of coding sequences ( Fig. 4A) [16,26].…”
Section: Increased Occupancy By Taf1 Upon Kin28 Depletion Is Suppressmentioning
confidence: 82%
See 3 more Smart Citations
“…We found that Taf1 occupancy was essentially unchanged upon simultaneous depletion of Kin28 and TBP (Fig. 4A); marked effects on Mediator and Pol II association provide evidence for efficient depletion of both Kin28 and TBP [21], as does the loss of the artifactual, transcription-dependent signal at the 3' ends of coding sequences ( Fig. 4A) [16,26].…”
Section: Increased Occupancy By Taf1 Upon Kin28 Depletion Is Suppressmentioning
confidence: 82%
“…To test whether the increased association of Taf1 seen upon Kin28 depletion requires stable TBP occupancy, we performed ChIP-seq against Taf1 in kin28-tbp-AA yeast, in which rapamycin addition causes depletion of both Kin28 and TBP [21]. We found that Taf1 occupancy was essentially unchanged upon simultaneous depletion of Kin28 and TBP (Fig.…”
Section: Increased Occupancy By Taf1 Upon Kin28 Depletion Is Suppressmentioning
confidence: 95%
See 2 more Smart Citations
“…The Tail module attaches to the core Mediator through the Med14 (Rgr1) scaffold subunit (Tsai et al 2014) and interacts with sequence-specific transcription factors that recruit the Mediator complex to the UAS or enhancers of genes (Bhoite et al 2001;Kagey et al 2010;Jeronimo and Robert 2014). The tail module is required for efficient recruitment of Mediator and Pol II to promoters (Knoll et al 2018).…”
Section: Introductionmentioning
confidence: 99%